THE USE OF AUDIO VISUAL MEDIA IN LEARNING ENGLISH TO IMPROVE STUDENTS’ LISTENING COMPREHENSION AT SEVENTH GRADE STUDENTS OF MTS NEGERI TARAKAN - Agustine, Diana Yulia (Borneo Journal of English Language Education, 2021)
The objective of the research was to find out whether using audio visual media can improve the students’ listening comprehension at seventh grade students ofMTs Negeri Tarakan. This research used CAR (Classroom Action Research) conductedin two cycles, each cycle consists of two meetings. The instrument of this researchwere observation checklist for teacher and students, and listening test. The result ofthe observation checklist for teacher got score in the first cycle, meeting I: 74(70.47%) and meeting II: 80 (746.19%) then, the second cycle the score in meeting I:83 (79.04%) and meeting II: 88 (81.90%). And The result of the students score in first cycle 19 (70.37%) students success to reach the minimum passed grade (KKM) and 8 (26.62%) students fail to reach the minimum passed grade. But insecond cycle there was improvement of the result of the students’ score in listeningcomprehension, can be seen from the result that 22 (81.48%) students success toreach the minimum passed grade and only 5 (18.51%) students fail to reach theminimum passed grade. The conclusion in this research by using audio visual media inlearning English can improve students’ listening comprehension especially for seventh grade students in MTs Negeri Tarakan. Keyword: Listening comprehension, audio visual media